Screening and Identification of an H-2Kb-Restricted CTL Epitope within the Glycoprotein of Hantaan Virus - Ma, Rui-xue; Cheng, Lin-feng; Ying, Qi-kang; Liu, Rong-rong; Ma, Tie-jun; Zhang, Xiao-xiao; Liu, Zi-yu; Zhang, Liang; Ye, Wei; Zhang, Fang-lin; Xu, Zhi-kai; Wang, Fang; et al. (Frontiers in Cellular and Infection Microbiology, 2016)
The cytotoxic T lymphocyte (CTL) response plays a key role in controlling viral infection, but only a few epitopes within the HTNV glycoprotein (GP) that are recognized by CTLs have been reported. In this study, we identified one murine HTNV GP-derived H2-Kb-restricted CTL epitope in C57BL/6 mice, which could be used to design preclinical studies of vaccines for HTNV infection. First, 15 8-mer peptides were selected from the HTNV GP amino acid sequence based on a percentile rank of <= 1% by IEDB which is the most comprehensive collection of epitope prediction and analysis tool. A lower percentile rank indicates higher affinity and higher immune response. In the case of the consensus method, we also evaluated the binding score of peptide-binding affinity by the BIMAS software to confirm that all peptides were able to bind H2-Kb. Second, one novel GP-derived CTL epitope, GP6 aa456-aa463 (ITSLFSLL), was identified in the splenocytes of HTNV-infected mice using the IFN-γ ELISPOT assay. Third, a single peptide vaccine was administered to C57BL/6 mice to evaluate the immunogenic potential of the identified peptides. ELISPOT and cell-mediated cytotoxicity assays showed that this peptide vaccine induced a strong IFN-γ response and potent cytotoxicity in immunized mice. Last, we demonstrated that the peptide-vaccinated mice had partial protection from challenge with HTNV. In conclusion, we identified an H2-Kb-restricted CTL epitope with involvement in the host immune response to HTNV infection.